Stocking densities and feeding strategies in shrimp and tilapia polyculture in tanks - Simão, Bruno Rodrigo; Brito, Luis Otavio; Maia, Alex Sandro Campos [UNESP]; Miranda, Laizy Cabral; Azevedo, Celicina Maria Da Silveira Borges (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 2013)
The objective of this work was to evaluate the performance of Pacific marine shrimp (Litopenaeus vannamei) and tilapia (Oreochromis niloticus), in a polyculture in tanks subjected to different stocking densities and feeding strategies, in comparison with monoculture. Two experiments were performed, at the same time, in a completely randomized design with three treatments and four replicates each. Treatments for experiment I were: monoculture with 10 shrimp per m² (10S:0T); polyculture with 10 shrimp and 0.5 tilapia per m² (10S:0.5T); and polyculture with 10 shrimp and 1 tilapia per m² (10S:1T). Shrimp was the main crop, and feed was provided based on shrimp biomass. Treatments for experiment II were: monoculture with 2 tilapia per m² (2T:0S); polyculture with 2 tilapia and 2.5 shrimp per m² (2T:2.5S); and polyculture with 2 tilapia and 5 shrimp per m² (2T:5S). Tilapia was the main crop, and feed was provided based on fish requirements. In the experiment I, tilapia introduction to shrimp culture resulted in lower shrimp growth and poor feed conversion rate. In experiment II, shrimp introduction to tilapia culture did not interfere with fish performance. Polyculture is more efficient with the combination of 2 tilapia and 2.5 or 5 shrimp per m² and feed based on fish requirements.

O objetivo deste trabalho foi avaliar o desempenho de camarão marinho (Litopenaeus vannamei) e tilápia (Oreochromis niloticus) em policultivo, em tanques de cimento, submetido a diferentes densidades de estocagem e estratégias de alimentação, em comparação ao monocultivo. Dois experimentos foram conduzidos, ao mesmo tempo, em delineamento inteiramente casualizado, com três tratamentos e quatro repetições cada um. Os tratamentos do experimento I foram: monocultivo com 10 camarões por m² (10S:0T); policultivo com 10 camarões e 0,5 tilápia por m² (10S:0.5T); e policultivo com 10 camarões e 1 tilápia por m² (10S:1T). O camarão foi a principal cultura, e a alimentação fornecida foi baseada na biomassa de camarão. Os tratamentos do experimento II foram: monocultivo com 2 tilápias por m² (2T:0S); policultivo com 2 tilápias e 2,5 camarões por m² (2T:2.5S); e policultivo com 2 tilápias e 5 camarões por m² (2T:5S). A tilápia foi a principal cultura, e a alimentação fornecida foi baseada na necessidade dos peixes. No experimento I, a introdução da tilápia no cultivo de camarão resultou em baixo crescimento do camarão e baixa taxa de conversão alimentar. No experimento II, a introdução de camarão no cultivo de tilápia não interferiu no desempenho dos peixes. O policultivo é mais eficiente com a combinação de 2 tilápias e 2,5 ou 5 camarões por m² e alimentação baseada na necessidade dos peixes.
Densidades de estocagem e estratégias de alimentação em policultivo de camarão e tilápia em tanques
Keywords: Litopenaeus vannamei; Oreochromis niloticus; eficiência aquícola; estratégia de alimentação; Litopenaeus vannamei; Oreochromis niloticus; aquaculture efficiency; feeding strategie